2014
DOI: 10.2215/cjn.08310813
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Body Mass Index with Access to Kidney Transplantation in Men and Women

Abstract: Background and objectives Obese patients encounter barriers to medical care not encountered by lean patients, and inequities in access to care among obese patients may vary by sex. This study aimed to determine the association of body mass index (BMI) with access to kidney transplantation in men and women.Design, setting, participants, & measurements In this retrospective analysis of 702,456 incident ESRD patients aged 18-70 years (captured in the US Renal Data System between 1995 and 2007), multivariate time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 33 publications
4
84
0
1
Order By: Relevance
“…A recent analysis of the US Renal Data System database that focused on obese patients with CKD showed that obese women have a lesser probability of receiving a kidney transplant than obese men. 9 This access disparity for obese women is further compounded by their greater likelihood of developing a highrisk panniculus, as also suggested by our study cohort's sex distribution.…”
Section: Surgery J 2015supporting
confidence: 59%
See 2 more Smart Citations
“…A recent analysis of the US Renal Data System database that focused on obese patients with CKD showed that obese women have a lesser probability of receiving a kidney transplant than obese men. 9 This access disparity for obese women is further compounded by their greater likelihood of developing a highrisk panniculus, as also suggested by our study cohort's sex distribution.…”
Section: Surgery J 2015supporting
confidence: 59%
“…This issue is even more relevant for patients with CKD, because prevalence of obesity in that group is much greater than in the general population to begin with, and because obesity in general has been shown to impair access to kidney transplantation. [7][8][9] At our transplant center, we attempted to provide patients with a high-risk panniculus with a realistic chance for a renal transplant and its cardiovascular morbidity-and mortality-lowering benefits. We developed a novel clinical pathway in collaboration with our plastic surgeons by devising a 2-stage approach that included panniculectomy followed by a transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further complicate this alarming situation, comorbidities can progress throughout ESRD [33], including those waitlisted for KT. Finally, other barriers to accessing KT, such as socio-demographic factors (obesity, female patients, patients who live in rural areas or far from transplant centers, among others) could increase the time on the WL and favor the onset or impairment of non-desirable comorbidities while still on the WL, leading to a higher mortality [19, 34-36]. However, there may be a high overlap in the risk profile and life-expectancy of patients waitlisted for KT and those who are not [24], suggesting that accurate assessment of the risk of death should be performed in order to prioritize or properly assign a KT.…”
Section: Risks Of Death On the Waiting-listmentioning
confidence: 99%
“…Gill et al (55) recently found that overweight and obese women are significantly less likely to receive LDKT compared with overweight and obese men. Despite these notable barriers, there does not appear to be a sex disparity in LDKT because women comprise 40% of the candidates on the transplant waiting list and are recipients of 39% of all kidney transplants annually (1).…”
Section: Sexmentioning
confidence: 99%